BIOCHEMICAL CHANGES DURING DRAFT LOADING IN DONKEYS - Moolchandani, Anil; Sareen, Meenakshi (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
The present investigation was carried out to study the effects of draft load on biochemical parameters glucose, cholesterol, urea and lactate in donkeys. Six male donkeys 4 to 5 years of age were subjected to loading exercise (i.e. 10 per cent draft load for 1st to 5th days and 20 per cent draft load from 6th to 10th day). A highly significant (P
Keywords: Draft load; Donkeys; Biochemical Parameters